2005
DOI: 10.1016/j.ygyno.2004.09.050
|View full text |Cite
|
Sign up to set email alerts
|

COX-2, c-KIT and HER-2/neu expression in uterine carcinosarcomas: prognostic factors or potential markers for targeted therapies?

Abstract: Objectives. Uterine carcinosarcomas are uncommon, highly aggressive neoplasms that frequently recur after surgical treatment and adjuvant chemo-radiotherapy. Patients with recurrent disease respond poorly to salvage chemotherapy and irradiation. New therapeutic options are required for patients with metastatic disease. Clinical evidences showing the effect of a tyrosine kinase inhibitor, STI571, in c-KIT-positive gastrointestinal tumors, the role of COX-inhibitors chemotherapy-associated in colorectal cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 38 publications
4
30
0
2
Order By: Relevance
“…The expression c-KIT for example, has been demonstrated in MMMTs (15)(16)(17)(18), but as this protein expression is not associated with KIT-activating mutation in exons 11 or 17, patients with uterine carcinosarcomas are not suitable candidates for treatment with imatinib (19). Similarly, immunohistochemical expression of HER-2 has been reported in a minority of uterine carcinosarcomas (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The expression c-KIT for example, has been demonstrated in MMMTs (15)(16)(17)(18), but as this protein expression is not associated with KIT-activating mutation in exons 11 or 17, patients with uterine carcinosarcomas are not suitable candidates for treatment with imatinib (19). Similarly, immunohistochemical expression of HER-2 has been reported in a minority of uterine carcinosarcomas (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…HER-2, EGFR, KIT) in some cases of CS, suggesting potential targets for therapeutic intervention in subgroups of CS [9][10][11][12][13][14]. However, serum markers have yet to be identified and evaluated for uterine carcinosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…1,14Y16 Only 2 studies assessed the effect of COX-2 expression on survival, and as in other gynecologic cancers, the results are conflicting. 1, 15 Raspollini et al 15 in a series of 24 patients found an association with vascular space involvement and with disease-free interval but, paradoxically, no association with stage. However, in contrast to our previous study 1 and to the present study of mature survival data, their patients with COX-2 expression showed significantly poorer survival.…”
Section: Discussionmentioning
confidence: 96%